Teaching and use of silver diamine fluoride in Pediatric Dentistry: a questionnaire-based crosssectional analysis of undergraduate Brazilian dental schools - Fröhlich, Tatiana Tambara; Leite, Taiane Costa; Rocha, Rachel de Oliveira (Revista da ABENO, 2022)
This study investigated the teaching and use of silver diamine fluoride (SDF) in Pediatric Dentistry in undergraduate Brazilian dental schools through a questionnaire-based cross-sectional analysis. Two-hundred and thirty-five questionnaires were e-mailed to directors of Pediatric Dentistry of undergraduate Brazilian dental schools. The details of the teaching and use of SDF in clinical practice were asked. Obtained data were analyzed descriptively and using the chi-square test. A total of 149 complete questionnaires were returned (63.4%). Most of schools taught SDF in lectures (73.8%, p <0.001). The majority use SDF in clinical practice (64.4%, p <0.001), but its use is not frequent (11.4%, p<0.001). All dental schools reported that SDF is applied in primary teeth, and few reported its use for permanent teeth (36.4%, p = 0.01). SDF has been used mainly for cavitated caries in primary teeth of children aged 0 to 3 years (93.7%, p<0.001), with restricted use in posterior teeth (42.7%, p <0.001). Although SDF is teaching and used in clinical practice in Pediatric Dentistry in most Brazilian undergraduate schools, its use is not frequent. Furthermore, SDF is not considered an option for caries lesions in some dental schools